Kebijakan Publik atas Penerapan Pajak Karbon di Indonesia - Editiana, Athaya Fitri (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
The impact of climate change has become a global challenge that needs to be addressed together. Indonesia is one of the countries vulnerable to climate change due to declining CO2 carbon emissions. The declining air quality in Indonesia is one of the reasons why carbon tax should be implemented immediately. The main objective of a carbon tax is to change the behavior of economic actors to shift to lower-carbon economic activities. In Indonesia, regulations on carbon tax have already been made. Regulations regarding carbon tax rules have been regulated in article 13 of Law Number 7 of 2021 concerning Harmonization of Tax Regulations. The purpose of this study is to provide an overview of the concept of carbon tax implementation in Indonesia. Methodology research methodology is a literature review. The data presented is secondary data obtained from internet sites, national seminar materials, and national and international journals. The result of the research is the concept of carbon tax implementation through emission trading using cap-and-trade scheme. Provisions regarding the procedures for calculating, collecting, paying or depositing, reporting, and mechanisms for imposing carbon tax, and procedures for reducing carbon tax and/or other treatment for fulfilling carbon tax obligations, are regulated by the Minister of Finance Regulation which is currently being prepared by the government.